SIRT6 safeguards human mesenchymal stem cells from oxidative stress by coactivating NRF2 - Pan, Huize; Guan, Di; Liu, Xiaomeng; Li, Jingyi; Wang, Lixia; Wu, Jun; Zhou, Junzhi; Zhang, Weizhou; Ren, Ruotong; Zhang, Weiqi; Li, Ying; Yang, Jiping; et al. (Cell research, 2016)
SIRT6 belongs to the mammalian homologs of Sir2 histone NAD＋-dependent deacylase family. In rodents, SIRT6 deficiency leads to aging-associated degeneration of mesodermal tissues. It remains unknown whether human SIRT6 has a direct role in maintaining the homeostasis of mesodermal tissues. To this end, we generated SIRT6 knockout hu- man mesenchymal stem cells （hMSCs） by targeted gene editing. SIRT6-deficient hMSCs exhibited accelerated func- tional decay, a feature distinct from typical premature cellular senescence. Rather than compromised chromosomal stability, SIRT6-null hMSCs were predominately characterized by dysregulated redox metabolism and increased sen- sitivity to the oxidative stress. In addition, we found SIRT6 in a protein complex with both nuclear factor erythroid 2-related factor 2 （NRF2） and RNA polymerase II, which was required for the transactivation of NRF2-regulated an- tioxidant genes, including heme oxygenase 1 （HO-1）. Overexpression of HO-1 in SIRT6-null hMSCs rescued prema- ture cellular attrition. Our study uncovers a novel function of SIRT6 in maintaining hMSC homeostasis by serving as a NRF2 coactivator, which represents a new layer of regulation of oxidative stress-associated stem cell decay.